2021
DOI: 10.1111/cpr.12976
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial extracellular matrix rigidity and IFNτ ensure the establishment of early pregnancy through activation of YAP

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…As we demonstrated above, the dynamic biomechanical nature of endometrial remodeling and the endometrial cell regeneration that occur during the repair of physiological or pathological uterine lesions are remarkable, but the mechanism by which cells in the endometrial cellular niche respond to mechanical cues remains unclear. We previously showed that YAP, as a sensor of chemical and mechanical cues, participates in the establishment of pregnancy [ 25 ]. Therefore, we speculate that YAP is involved in the conversion of mechanical signals to chemical cues during the uterine repair process.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As we demonstrated above, the dynamic biomechanical nature of endometrial remodeling and the endometrial cell regeneration that occur during the repair of physiological or pathological uterine lesions are remarkable, but the mechanism by which cells in the endometrial cellular niche respond to mechanical cues remains unclear. We previously showed that YAP, as a sensor of chemical and mechanical cues, participates in the establishment of pregnancy [ 25 ]. Therefore, we speculate that YAP is involved in the conversion of mechanical signals to chemical cues during the uterine repair process.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, cell proliferation was not completely suppressed, and it remains unclear whether this was due to incomplete inhibition or whether other cues that are independent of F-actin are involved in the repair of the endometrium. For example, the classical Hippo-YAP pathway is regulated by chemical signals, and the WNT signaling pathway regulates stem cell activation and proliferation[ 25 , 33 , 34 ]. Together, these data indicate that blocking the mechanotransduction pathway leads to prolongation of the time required for uterine repair.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations